Has the COVID-19 Pandemic Caused Upshifting in Colorectal Cancer Stage? - Ji Ha Lim; Woo Yong Lee; Seong Hyeon Yun; Hee Cheol Kim; Yong Beom Cho; Jung Wook Huh; Yoon Ah Park; Jung Kyong Shin (Annals of Coloproctology, 2021)
Purpose Coronavirus disease 2019 (COVID-19) has affected many parts of daily life and healthcare, including cancer screening and diagnosis. The purpose of this study was to determine whether there was an upshift in the colorectal cancer stage at diagnosis due to delays related to the COVID-19 outbreak. Methods From January to June of each year from 2017 to 2020, a total of 3,229 patients who were first diagnosed with colorectal cancer were retrospectively reviewed. Those enrolled from 2017 to 2019 were classified as the ‘pre-COVID’ group, and those enrolled in 2020 were classified as the ‘COVID’ group. The primary outcome was the rate of stage IV disease at the time of diagnosis. Results There was no statistically significant difference in the proportion of stage IV patients between the pre-COVID and COVID groups (P=0.19). The median preoperative carcinoembryonic antigen level in the COVID group was higher than in the pre-COVID group in all stages (all P<0.05). In stage I, II patients who underwent radical surgery, the lymphatic invasion was more presented in COVID patients (P=0.009). Conclusion We did not find significant stage upshifting in colorectal cancer during the COVID-19 outbreak. However, there were more initially unresectable stage IV colorectal cancer patients with a low conversion rate to resectable status, and more patients had factors related to poor prognosis. These results may become more apparent over time, so it is vital not to neglect cancer screening to not delay the diagnosis during the COVID-19 epidemic.